2022
DOI: 10.1002/cmdc.202200091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Radiolabeled Macrocyclic Peptide as Potential PET Imaging Probe for PD−L1

Abstract: The interaction between the immune checkpoint PD-1 and PDÀ L1 promotes T-cell deactivation and cancer proliferation. Therefore, immune checkpoint inhibition therapy, which relies on prior assessment of the target, has been widely used for many cancers. As a non-invasive molecular imaging tool, radiotracers bring novel information on the in vivo expression of biomarkers (e. g., PDÀ L1), enabling a personalized treatment of patients. Our work aimed at the development of a PDÀ L1specific, peptide-based PET radiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…[ 68 Ga]Ga-NJMP1 68 Ga PET 25.9 µM [63] Small Molecule [ 18 F]FLN 18 F PET 65.3 nM [64] [ 18 F]FLG-1 18 F 63.1 nM [65] HAC-PD1 DOTA-HAC 64 Cu PET ~110 pM [66] NOTA-HAC NOTA-HACA DOTA-HACA 1 Values for non-conjugated Atezolizumab. 2 Value for unsubstituted peptide; K D for substituted peptide was found to be in the same range.…”
Section: Pd-l1mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 68 Ga]Ga-NJMP1 68 Ga PET 25.9 µM [63] Small Molecule [ 18 F]FLN 18 F PET 65.3 nM [64] [ 18 F]FLG-1 18 F 63.1 nM [65] HAC-PD1 DOTA-HAC 64 Cu PET ~110 pM [66] NOTA-HAC NOTA-HACA DOTA-HACA 1 Values for non-conjugated Atezolizumab. 2 Value for unsubstituted peptide; K D for substituted peptide was found to be in the same range.…”
Section: Pd-l1mentioning
confidence: 99%
“…Therefore, these results are promising for quantifying PD-L1 levels clinically for patient stratification and therapeutic monitoring. Inspired by the promising results of the cyclic peptides, Jouini et al developed a PD-L1-specific macrocyclic peptide NJMP1 based on a structure reported in a patent from Bristol Myers Squibb [63]. The 68 Ga-labeled peptide was studied on CHO-K1 hPD-L1 cells but showed very low cell binding and internalization rates in comparison to those of the control radiopeptide WL12.…”
Section: Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of radiolabeled anti-PD-L1 antibodies, nanobodies, and small inhibitors to image PD-L1 expression have been demonstrated in different tumor models [ 11 , 12 , 13 , 14 , 15 ]. Atezolizumab [ 16 ], the first FDA-approved PD-L1 mAbs, has been utilized for PET imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Single photon emission computed tomography (SPECT) and positron emission tomography (PET) imaging can definitely resolve the practical issues encountered with IHC and provide a noninvasive method to detect PD-L1 expression with whole-body imaging dynamically and accurately. Previous studies of immune-PET probes with antibodies to PD-L1 labeled with positron-emitting radionuclides (fluorine-18, copper-64, and zirconium-89, etc.) demonstrated that PET imaging could provide precise information on the PD-L1 status in all tumor lesions of cancer patients. Despite its quantitative and radiochemical advantages, the availability of PET has remained rather limited due to the higher cost of the scanners, the cyclotron, and radiochemistry. , The popularization of immunotherapy requires the cheaper, more widely available, and routinely used clinical tool SPECT to detect PD-L1 expression, which is conducive to the widespread application at any standard hospital radiopharmacy.…”
Section: Introductionmentioning
confidence: 99%